Comparative Study of Watertight and Non-Watertight Duraplasty for Decompressive Craniectomy in Traumatic Brain Injury: A Prospective Study - Shakya, Bikram; KC, Bidur (Nepal Journal of Neuroscience, 2001)
Introduction: This prospective study aimed to compare the efficacy and safety of watertight versus non-watertight duraplasty techniques in patients undergoing decompressive craniectomy (DC) for severe traumatic brain injury (TBI).Material and Methods: We evaluated 48 patients with severe TBI who underwent DC, with 24 receiving watertight duraplasty and 24 receiving non-watertight duraplasty. Primary outcomes included the incidence of cerebrospinal fluid (CSF) leaks, postoperative infections, and wound healing disturbances. Secondary outcomes included operative duration, ICU stay, hospital stay, mortality, and Glasgow Outcome Scale (GOS) scores at 6 months post-surgery. Data were compared using appropriate statistical tests, and results were benchmarked against international publications.Results: Watertight duraplasty significantly reduced the incidence of CSF leaks (8.3% vs. 29.2%, P=0.041) and shortened hospital stay (22.8 ± 6.3 days vs. 28.4 ± 7.2 days, P=0.027) compared to non-watertight duraplasty. Although the watertight group had fewer postoperative infections (12.5% vs. 25.0%) and wound healing disturbances (8.3% vs. 20.8%), these differences were not statistically significant. The operative duration was longer for the watertight group (145 ± 25 minutes vs. 115 ± 20 minutes, p